2021
DOI: 10.3390/biology10080806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extender, Storage Time and Temperature on Kinetic Parameters (CASA) on Bull Semen Samples

Abstract: CASA kinetic parameters are often evaluated in a diagnostic centre. How storage conditions affect ejaculates up to evaluation is unclear. We assessed, in 25 commercial bulls electroejaculated in the field, the impact of time until evaluation (0–2 h, 4–6 h, and 24 h post-ejaculation), holding temperature (5 °C vs. room temperature), and extender (AndroMed®, BIOXcell® or INRA96®) on CASA kinetic parameters. Total and progressive motility, VCL, VAP, VCL, ALH, BCF, STR, LIN, and WOB were assessed. CASA kinetic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…These results may be due to the different of fresh egg yolk and freeze-dried egg yolk composition of extender. Our results were consistent with the other research that described that sperm motility and kinetic parameters present difference when using different extenders (Farrell et al, 1998;Fernandez-Novo et al, 2021;Kumar et al, 2015;Miguel-Jimenez et al, 2020;Naz et al, 2018;Singh et al, 2018). The previous studies used 20% of lyophilized egg yolk based extenders containing various antioxidants on sperm cryopreservation quality in goats.…”
Section: Discussionsupporting
confidence: 93%
“…These results may be due to the different of fresh egg yolk and freeze-dried egg yolk composition of extender. Our results were consistent with the other research that described that sperm motility and kinetic parameters present difference when using different extenders (Farrell et al, 1998;Fernandez-Novo et al, 2021;Kumar et al, 2015;Miguel-Jimenez et al, 2020;Naz et al, 2018;Singh et al, 2018). The previous studies used 20% of lyophilized egg yolk based extenders containing various antioxidants on sperm cryopreservation quality in goats.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these parameters are linked to genetic factors, and the breed of the bull can influence results (Terán et al, 2021). Moreover, solutions in which sperm are suspended and processed can influence these variables and cause alterations in measurements depending on the semen extender used for the samples (Fernandes et al, 2021; Fernandez‐Novo et al, 2021). The evaluation of the semen extenders by breed can be useful for determining the adequate diluent and maximizing the fertilizing potential.…”
Section: Discussionmentioning
confidence: 99%
“…OptiXcell® semen extender presented less variation because the PFA clustered the spermatozoa into two subpopulations. Some authors have suggested that extenders influence clustering because of their influence on morphometric values (Fernandez‐Novo et al, 2021; Marinović et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although sperm may be kept for long periods, its quality may gradually deteriorate with time. This reduction may be caused by elements including temperature swings, storage conditions, and the amount of time spent in storage [9].…”
Section: Introductionmentioning
confidence: 99%